Lecture Attendance among Undergraduate Business Students in Egypt: An Exploratory Study - José-Louis Iparraguirre; Álvaro Antón-Sancho; Diego Vergara (Education Sciences, 2023)
In Egypt’s higher education system, there are differences among universities about the compulsory nature of class attendance. In addition, the COVID-19 pandemic, which saw a transition of higher education activities to online environments, has led, after the return to face-to-face learning, to an update on the usefulness of face-to-face learning for higher education students. This work provides quantitative exploratory research on the assessment of university students in the areas of economics and business in Egypt about attendance to face-to-face lectures, its advantages and disadvantages, and the usefulness of implementing new learning methodologies within the lectures. As a result, it has been obtained that the participating students valued attendance as an important element of their learning, although they identified disadvantages in this regard. In addition, they supported the development of active and collaborative methodologies in lectures. It is proposed that this research should be extended to compare the results with those of other geographical areas, and it is suggested that universities increase the adoption of new learning methodologies through the adoption of measures, such as teacher training, in this regard.